Methodology to generate community learning through the participatory design of a boardgame - Torres, Karoline (2022)
Introduction. Didactic games are a powerful tool in formal and non-formal educational contexts. This study applies a general methodology based on the participative design of a didactic boardgame to facilitate an educational environment for community learning. Methods. Eighteen elderly people without housing participated in the study, all users of the shelter Centro Dormitorio Municipal San José in Costa Rica. Instruments such as interviews, dialogue circles, mental maps, brainstorm circles, and checkpoints were applied. A field diary and participant observation were used as data collection techniques. Participants worked together, along researchers, to design a board game during weekly meetings for a period of 1.6 years. Results. The board game potentialized three socio-emotional abilities identified as needs during the study for this elderly population (self-regulation, self-motivation, and self-knowledge). Discussion. A holistic vision, in our approach and methodology, were vital to achieve the universal reach expected from the methodology developed in this study. Here, we present a methodology that can be applied in various contexts to achieve the participatory creative design of a didactic boardgame and create the opportunity of community learning.